Rapid Single-Step Immunochromatographic Assay for Angiostrongylus cantonensis Specific Antigen Detection - Praphathip Eamsobhana; Anchalee Tungtrongchitr; Darawan Wanachiwanawin; Sudarat Boonyong; Hoi-Sen Yong (Pathogens, 2023)
Angiostrongylus cantonensis is the major etiological nematode parasite causing eosinophilic meningitis and/or eosinophilic meningoencephalitis in humans. The rapid global spread of Angiostrongylus cantonensis and the emerging occurrence of the infection have exposed the shortcomings of traditional/conventional diagnostics. This has spurred efforts to develop faster, simpler and more scalable platforms that can be decentralized for point-of-need laboratory testing. By far, the point-of-care immunoassays such as the lateral flow assay (LFA) are the best-placed. In this work, a LFA in the form of an immunochromatographic test device (designated AcAgQuickDx), based on the detection of a circulating Angiostrongylus cantonensis-derived antigen, was established using anti-31 kDa Angiostrongylus cantonensis antibody as the capture reagent and anti-Angiostrongylus cantonensis polyclonal antibody as the indicator reagent. The AcAgQuickDx was evaluated for its diagnostic potential with a total of 20 cerebrospinal fluids (CSF) and 105 serum samples from patients with angiostrongyliasis and other clinically related parasitic diseases, as well as serum samples from normal healthy subjects. Three of the ten CSF samples from serologically confirmed angiostrongyliasis cases and two of the five suspected cases with negative anti-Angiostrongylus cantonensis antibodies showed a positive AcAgQuickDx reaction. Likewise, the AcAgQuickDx was able to detect Angiostrongylus cantonensis specific antigens in four serum samples of the 27 serologically confirmed angiostrongyliasis cases. No positive reaction by AcAgQuickDx was observed in any of the CSF (n = 5) and serum (n = 43) samples with other parasitic infections, or the normal healthy controls (n = 35). The AcAgQuickDx enabled the rapid detection of active/acute Angiostrongylus cantonensis infection. It is easy to use, can be transported at room temperature and does not require refrigeration for long-term stability over a wide range of climate. It can supplement existing diagnostic tests for neuroangiostrongyliasis under clinical or field environments, particularly in remote and resource-poor areas.